Dongkrek Art in Rituals Ceremony in Mejayan Village, Caruban Sub-District, Madiun Regency - Moh Sarjoko; Sunarto Sunarto; Djuli Djatiprambudi; Suharto Suharto (International Conference on Science, Education, and Technology, 2023)
This study aims to find out and describe the role of dongkrek traditional art in village clean rituals. Research using descriptive method with a qualitative approach. Data collection tools are interviews, observation, and documentation. The process of data analysis by reducing, presenting, and concluding data. The results of the study show that (a) the traditional art of Dongkrek maintains the authenticity of the traditional Dongkrek art; (b) The procedure for performing the Dongkrek traditional art is divided into three stages, namely the pre-event stage, the main event stage and the closing stage; (c) The moral values ​​contained in the traditional arts of Dongkrek include the value of togetherness/mutual cooperation, the value of beauty, the value of truth, the value of kindness, the value of responsibility, the value of obedience, the value of bad or evil, the value of honesty, the value of trust; (d) The community of Mejayan Village is very supportive because the function of the traditional Dongkrek art is considered to be very potential as a spectacle and guide for the community.